2004
DOI: 10.1152/ajpheart.00164.2004
|View full text |Cite
|
Sign up to set email alerts
|

Redox active hemoglobin enhances lipopolysaccharide-induced injury to cultured bovine endothelial cells

Abstract: D'Agnillo, Felice. Redox active hemoglobin enhances lipopolysaccharide-induced injury to cultured bovine endothelial cells. Am J Physiol Heart Circ Physiol 287: H1875-H1882, 2004. First published June 17, 2004 10.1152/ajpheart.00164.2004.-The interaction of cell-free hemoglobin with lipopolysaccharide (LPS) is thought to aggravate the pathophysiology of sepsis and/or septic shock. This study examines the possible modulatory role of cell-free hemoglobin on LPS-induced apoptosis of cultured bovine aortic endoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…In the context of the present study, we postulate that the oxidative microenvironment created by activated circulating inflammatory cells or tissue resident cells along the endothelial lining and within perivascular sites could be a major factor driving the oxidative reactions of Hb or its breakdown products [31]. Consistent with this view, the enhanced redox activity of various Hbs was shown to dramatically enhance LPS-induced apoptosis in endothelial cell culture [32]. Endothelial dysfunction is a hallmark of sepsis, which is often characterized by increased vascular permeability induced by LPS-mediated processes in several tissues, including the right and left ventricular coronary micro-vasculature [33,34].…”
Section: Discussionsupporting
confidence: 59%
“…In the context of the present study, we postulate that the oxidative microenvironment created by activated circulating inflammatory cells or tissue resident cells along the endothelial lining and within perivascular sites could be a major factor driving the oxidative reactions of Hb or its breakdown products [31]. Consistent with this view, the enhanced redox activity of various Hbs was shown to dramatically enhance LPS-induced apoptosis in endothelial cell culture [32]. Endothelial dysfunction is a hallmark of sepsis, which is often characterized by increased vascular permeability induced by LPS-mediated processes in several tissues, including the right and left ventricular coronary micro-vasculature [33,34].…”
Section: Discussionsupporting
confidence: 59%
“…Bolus additions of hydrogen peroxide and Hb to cells lead to glutathione depletion (67). In ischemia=reperfusion models of endothelial cells in culture, the formation of ferryl Hb was linked to cellular lipid oxidation (172).…”
Section: A the Rational Design Of Hemoglobin-based Oxygen Carriersmentioning
confidence: 99%
“…These data are in accordance with data from Roth et al [11] who demonstrated also clear changes in electron micrographs after addition of Hb compatible with a disaggregation. D'Agnillo [33] has studied the effect of various Hb structures and LPS on apoptosis, and found only in the absence of serum any effect. These data were interpreted by an effect of redox active Hb, driven by the low level of oxidative stress, thus exacerbating the LPS-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%